Changes in acute pulmonary vascular responsiveness to hypoxia during a progressive ascent to high altitude (5300 m). Issue 6 (21st May 2017) - Luks, Andrew M.; Levett, Denny; Martin, Daniel S.; Goss, Christopher H.; Mitchell, Kay; Fernandez, Bernadette O.; Feelisch, Martin; Grocott, Michael P.; Swenson, Erik R.; ,
Abstract : New Findings: What is the central question of this study? Do the pulmonary vascular responses to hypoxia change during progressive exposure to high altitude and can alterations in these responses be related to changes in concentrations of circulating biomarkers that affect the pulmonary circulation? What is the main finding and its importance? In our field study with healthy volunteers, we demonstrate changes in pulmonary artery pressure suggestive of remodelling in the pulmonary circulation, but find no changes in the acute responsiveness of the pulmonary circulation to changes in oxygenation during 2 weeks of exposure to progressive hypoxia. Pulmonary artery pressure changes were associated with changes in erythropoietin, 8‐isoprostane, nitrite and guanosine 3′, 5′‐cyclic monophosphate. We sought to determine whether changes in pulmonary artery pressure responses to hypoxia suggestive of vascular remodelling occur during progressive exposure to high altitude and whether such alterations are related to changes in concentrations of circulating biomarkers with known or suspected actions on the pulmonary vasculature during ascent. We measured tricuspid valve transvalvular pressure gradients (TVPG) in healthy volunteers breathing air at sea level (London, UK) and in hypoxic conditions simulating the inspired O2 partial pressures at two locations in Nepal, Namche Bazaar (NB, elevation 3500 m) and Everest Base Camp (EBC, elevation 5300 m). During a subsequent 13 day trek, TVPG was measured at NB and EBC while volunteers breathed air and hyperoxic or hypoxic mixtures simulating the inspired O2 partial pressures at the other locations. For each location, we determined the slope of the relationship between TVPG and arterial oxygen saturation ( S a O 2 ) to estimate the pulmonary vascular response to hypoxia. Mean TVPG breathing air was higher at any S a O 2 at EBC than at sea level or NB, but there was no change in the slope of the relationship between S a O 2 and TVPG between locations. Nitric oxide availability remained unchanged despite increases in oxidative stress (elevated 8‐isoprostane). Erythropoietin, pro‐atrial natriuretic peptide and interleukin‐18 levels progressively increased on ascent. Associations with TVPG were observed only with erythropoietin, 8‐isoprostane, nitrite and guanosine 3′, 5′‐cyclic monophosphate. Although the increased TVPG for any given S a O 2 at EBC suggests that pulmonary vascular remodelling might occur during 2 weeks of progressive hypoxia, the lack of change in the slope of the relationship between TVPG and S a O 2 indicates that the acute pulmonary vascular responsiveness to changes in oxygenation does not vary within this time frame. Abstract :